Changes in the content of Finnish municipal occupations over a four-year period. - Huuhtanen, P.; Nygard, C. H.; Tuomi, Kaija; Eskelinen, Leena; Toikkanen, J. (Scandinavian Journal of Work, Environment & Health, 1991)
The data of this study are based on questionnaire surveys made in 1981 and 1985. The sample consisted of 1799 men and 2456 women in the age range of 48-62 years. Physical demands were more common in 1985 than in 1981, and more common among the women than among the men. In addition problems with the physical-chemical environment were more common in 1985 and more common among the men. The changes in tasks were evaluated more often as positive than negative. The mental load had increased between 1981 and 1985 due to an increase in the amount of work and the knowledge needed at work. In addition changes in social contacts and client relations increased the mental load.